1991
DOI: 10.1557/s0883769400056049
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Sensitive Polymers and Hydrogels

Abstract: Environmentally sensitive polymers and hydrogels exhibit sharp changes in behavior in response to relatively small changes in conditions such as temperature or pH. Typical changes include precipitation of the polymer in water or collapse of a hydrogel with expulsion of a large fraction of the gel pore water. These changes are depicted in Figure 1. If such a polymer is grafted or adsorbed on another polymer surface or within the pores of a porous membrane, then one observes sharp changes in wettability or perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 39 publications
2
86
0
Order By: Relevance
“…The data indicate that all XMNs have a higher LCST than the pure PNIPAAm hydrogel(XMN0) at 33 ℃ [10].…”
Section: Lcst Of Xan-ma/pnipaam Hybrid Hydrogelsmentioning
confidence: 93%
“…The data indicate that all XMNs have a higher LCST than the pure PNIPAAm hydrogel(XMN0) at 33 ℃ [10].…”
Section: Lcst Of Xan-ma/pnipaam Hybrid Hydrogelsmentioning
confidence: 93%
“…Cross-linking density can be increased to improve the properties of the hydrogel, but crosslinking generally makes materials stiffer or embrittled (Tienen et al, 2004). Research has shown that the type (ionic versus covalent), number, and length of cross-linking in hydrogels can dramatically affect the elastic moduli and toughness of the system (Hoffman, 1991). Another route to strengthening the material involves utilizing a reinforcement material such as fabric or foam (Liu et al, 2008), but this may introduce stress risers into the material (Mansmann, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Among the family of temperature intelligent hydrogels, poly(Nisopropylacrylamide) (PNIPAAm) hydrogel is one of the most widely studied. It exhibits a lower critical solution temperature (LCST) or transition temperature (T tr ) at B33 C in aqueous solution and shows an abrupt thermoreversible change in volume as external temperature cycles around this critical temperature [14,15].…”
Section: Introductionmentioning
confidence: 99%